THE INFLUENCE OF WORK MORALE, LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE OF THE KUPANG CITY LOCAL GOVERNMENT ADMINISTRATION SECTION THROUGH JOB SATISFACTION AS A MEDIATING VARIABLE - Dewi Fitriani; Henny A. Manafe; Yolinda Yanti Sonbay (Jurnal Ekonomi, 2023)
Performance is necessary because it reflects an employee's capacity to complete assigned duties. According to the performance achievements of the Kupang City Regional Secretariat Governance Section employees over the past three years, employee performance in the Kupang City Regional Secretariat Governance Section has declined and is believed to be influenced by work enthusiasm, leadership, organizational culture, and job satisfaction. This investigation seeks to establish: 1) Respondents' perceptions of morale, leadership, organizational culture, job satisfaction, and employee performance in the Kupang City Local Government Administration Section; 2) The significance of the influence of work spirit, leadership, and organizational culture on job satisfaction; 3) The significance of the influence of job satisfaction on employee performance; and 4) The significance of the influence of job satisfaction on employee performance. Descriptive statistical analysis reveals that the variables of work zeal, leadership, job satisfaction, and performance are quite favorable. The perception of organizational culture variables, however, is positive. Work enthusiasm affects employee performance; leadership has no effect on employee performance; organizational culture has no effect on employee performance; job satisfaction affects employee performance; and work enthusiasm has a significant effect on job satisfaction.